India’s Innovation Policy: Current State and Features of the Indian Model - Shavlay, E. P. (Modernizat͡s︡ii͡a︡, innovat͡s︡ii, razvitie, 2020)
Purpose : this article analyzes India’s innovation development model. In this regard, the author aims to examine the current state of India's innovation policy as well as its features as one of the tools for solving the socio-economic problems of the state. Methods : the author applies general scientific methods of logical analysis, comparison and generalization, as well as quantitative methods (graphical and tabular methods, and descriptive statistics). In addition, the article embraces a systematic approach that contributes to a holistic consideration of the research subject. Results : the article provides an overview of the fundamental documents and projects of the state's innovation policy, studies India’s positions in world innovation ratings as well as notes the unique features of the Indian model of innovative development associated with the government strategy adjusted to the socio-economic, cultural and civilizational features of this country. Conclusions and Relevance : the article addresses the distinguishing characteristics which have eventually become disadvantages of the existing system and touches upon the reasons that hinder the development of innovations and prevent the country from achieving tangible results in this domain. The author concludes that without systematic government support, appropriate staffing, and functioning triple helix model involving academia, industry, and government, the country's innovative development will be limited, and India will fail to address the ever-widening gap between grassroots and high-tech innovation sectors will continue to grow. Still, Russia may learn a lot from the Indian experience as it also aims at solving its “grand challenges”, including those of social and economic nature, by the means of innovations.